'We need to put what we do in my dad's language, in pounds, shillings and pence': Commercialisation and the reshaping of public-sector planning in England. (February 2022) - Slade, Jason; Tait, Malcolm; Inch, Andy
This article furthers understanding of how commercial imperatives are reshaping dominant conceptions of planning practice in England, and by extension the production of the built environment more widely. We make an original contribution by tracing the emergence of the logic of commercialisation in England, demonstrating how the impacts of austerity and 'market-led viability planning' have entrenched the 'delivery state', a powerful disciplinary matrix representing late-neoliberal governance. Through in-depth, ethnographic study of a local planning authority, we argue that commercialisation within the delivery state creates a distinct 'economy of attention', reshaping planners' agency and professional identities, and the substance and scope of their work. The conclusion draws out wider implications of commercialisation for planning in and beyond the delivery state.